The Sound of the Suburbs: A Case Study of Three Garage Bands in San Jose, California during the 1960s. - Kauppila, Paul (Popular Music & Society, 2005)
The Chocolate Watchband, the Count Five, and the Syndicate of Sound were three garage bands from San Jose, California. During the 1960s, before the high-tech economy transformed the Santa Clara Valley into Silicon Valley, San Jose was a culturally sleepy suburb. This paper will examine these three groups in the context of 1960s culture and society and will compare and contrast their image and musical output with that of the better-known “hippie” music scene originating an hour north in San Francisco.